Family Trip to Sequoia National Park in 1924 Model T Ford - Watkins, Howard::::::::: (1978)
Rose Watkins, Albert Watkins, Christine Watkins, Adam Watkins, Howard Watkins at base of General Grant Giant Sequoia Tree The Nation's Christmas Tree